Improving Student Literacy Skills Through Visual Communication Media - Khoirul Alam; Undang Suryatna; Ali Alamsyah Kusumadinata (Universitas Djuanda, 2020)
The aim of this study was to comprehends students’ literacy abilities through visual communication media. Indicator of the assessment literacy ability based on the PISA institution in 2009 – 2015. The research was conducted at SDIT Insantama Bogor in 2018/2019 academic years. The research approach used quantitative which used sensus in five class elementery school. Total sampel in the case were 126 students. One-Grop Pretest-Posttest Design methode was used in the research. Simple linear regression was used in analysis process. The result of regression R = 0,886 showed correlation between an improving students’ literacy skills with Visual Communication Media (X) is strong and positive. Then, from the result of ANOVA data processing, showed: F Calculated was 148.380 with a significant level 0,000. Because the probability (0,000) was much smaller than 0,05, so the regression model can be used to predict an improving students’ literacy skills. The conclusion was there are significant influence on improving students’ literacy skills.